THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION OF MAXIM ONLINE TRANSPORTATION AT PAPUA CHRISTIAN UNIVERSITY - Andrei Maryen; Rendi Y Pattiasina; Oktovina Klasafle (RADJA PUBLIKA, 2025)
The purpose of this study was to determine the effect of service quality and price on customer satisfaction among Maxim online transportation users among management students. The sample size was 74, and the analysis technique used was multiple linear regression. The results showed that the First Hypothesis (H1): There is no effect of service quality (X1) on customer satisfaction (Y) among Maxim online transportation users among management students. This finding was not supported. This finding was based on the results of a T-test with a calculated T-value of 0.358 < T-table 1.666 and a significant value greater than 0.05 (0.209 > 0.05). The Second Hypothesis (H2): There is an effect of price (X2) on customer satisfaction among Maxim online transportation users among management students. This finding was supported. This finding was based on the results of a T-test with a calculated T-value of 2.923 > T-table 2.052 and a significant value less than 0.05 (0.007 < 0.05). Third Hypothesis (H3): There is an influence of service quality and price on customer satisfaction among Maxim online transportation users among management students, supported. This finding is based on the results of the F test, which obtained a calculated F value of 36.348 > F table 2.73 and a significance value less than 0.05 (0.000 < 0.05).